2013 Fifth International Conference on Communication Systems and Networks (COMSNETS) 2013
DOI: 10.1109/comsnets.2013.6465599
|View full text |Cite
|
Sign up to set email alerts
|

Provenance framework for mHealth

Abstract: Abstract-Mobile health technologies allow patients to collect their health information outside the hospital and share this information with others. But how can data consumers know whether to trust the sensor-collected and human-entered data they receive? Data consumers might be able to verify the accuracy and authenticity of the data if they have information about its origin and about changes made to it, i.e., the provenance of the data. We propose a provenance framework for mHealth devices, to collect and sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…For a blood-pressure reading, for example, it is important to know whether the subject applied the cuff correctly to her arm, rested her arm on a flat surface, and remained still throughout the reading. Aarathi Prasad and her colleagues proposed one approach to the specification and collection of contextual evidence for mHealth sensor data, 14 but much more needs to be done to recognize the many factors that affect the quality of such data. 15

Research challenge: develop extensible methods for collecting, storing, and presenting contextual information along with health-related data collected by mHealth devices and apps to help data consumers verify and interpret the health data.

…”
Section: Accuracy and Data Provenancementioning
confidence: 99%
“…For a blood-pressure reading, for example, it is important to know whether the subject applied the cuff correctly to her arm, rested her arm on a flat surface, and remained still throughout the reading. Aarathi Prasad and her colleagues proposed one approach to the specification and collection of contextual evidence for mHealth sensor data, 14 but much more needs to be done to recognize the many factors that affect the quality of such data. 15

Research challenge: develop extensible methods for collecting, storing, and presenting contextual information along with health-related data collected by mHealth devices and apps to help data consumers verify and interpret the health data.

…”
Section: Accuracy and Data Provenancementioning
confidence: 99%
“…The framework provides mechanisms based on Attribute Based Encrypyion (ABE) for scalable key management, flexible access for multiple classes of data consumers, and efficient user revocation. In [14], the authors propose a detailed data provenance framework to collect and share provenance metadata for patient health records, to help data consumers verify the accuracy and authenticity of the data and track its origins and changes made to it. However, the framework does not define and address a threat model.…”
Section: Related Workmentioning
confidence: 99%
“…All 17 studies were found in the SLR process together with the snowball technique, which are [ 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ] and are focused on managing provenance data in HISs. In Table 10 , the similarities of the 17 studies are observed in the following characteristics that contribute to the management of provenance data in HISs: use of models from the W3C PROV family; use of different models from the W3C PROV family; use of provenance techniques with blockchain; and use of provenance techniques with middleware.…”
Section: Similarities Of the Selected Studiesmentioning
confidence: 99%
“…It is important to emphasize that the types of HISs shown in Figure 5 have different characteristics, as detailed in this study. Moreover, based on the information in Figure 5 , the authors who mentioned the types of HISs in their studies in relation to the management of provenance data in the selected studies are as follows: EHRs [ 93 , 94 , 95 , 96 , 103 , 106 ]; PHRs [ 90 , 97 , 99 , 100 , 101 , 102 , 104 ]; the LHS [ 98 ]; HMSs [ 92 ]; the CRIS [ 91 ]; and the HIS [ 105 ].…”
Section: Systematic Literature Review Reportmentioning
confidence: 99%